Changing family structures/values and the incidence of human trafficking in Edo State (2007)
This paper attempts to unravel the underpinning factors that account for the upsurge of human trafficking in Edo State, Nigeria. The discourse is hinged on the Mertonian concept of innovation which explains the circumvention of societal mainstream values and employed as a circuit and routes to achieving societies collectively subscribed goals. The aims and objectives of the study include: identifying the changes in family structures that predispose parents to trafficking their children; examining the changes in family values that predispose parents to trafficking; discussing the perception of parents about trafficking their children and finally explaining the reasons for the persistence of human trafficking despite attempts to curb it. Focus group discussion (FGD) and in-depth interview methods were used in collecting data. The study revealed that parents are predisposed to trafficking their children due to poverty, unemployment, greed, ignorance, illiteracy, polygyny, distortion of social values, dysfunctional families among others